Strategic Importance of Air Transport in the Covid-19 Pandemic Process - Macit, Armağan (Journal of Applied And Theoretical Social Sciences, 2021)
Starting in China at the end of 2019, the corona virus disease, which affected the whole world, was declared as a global pandemic and had an important and negative impact in human history. The global crisis, which emerged with the effect of the pandemic, brought with it an economic crisis, and many sectors faced the devastating effect of the pandemic. One of the foremost of these sectors was undoubtedly the aviation sector. Within the scope of the measures, the closure of the borders and the prevention of international travels brought the global air traffic to a standstill and caused great destruction. In this context, aviation experts and academics focused on the devastating impact of the pandemic on the industry, focusing on the losses and recovery scenarios of the aviation industry. However, from a different perspective, air transport has played a leading role in very important activities during the pandemic period. At the beginning of the pandemic, air transport has shown its importance in issues such as evacuation flights for the citizens of each country, supply of test kits, controlled transportation to prevent disruptions in the supply chain, distribution of vaccines and the use of unmanned aerial vehicles. In this study, it is aimed to investigate how air transport is used by the states and the strategic support it provides to the states during the pandemic process. The strategic importance of air transport during the Covid-19 pandemic period will be revealed with examples from different parts of the world, especially Turkey.